(untitled) (Academicia Globe: Inderscience Research, 2021)
In this article we will study a methodology called communicative language teaching or CLT. We will also look at and analyze the impact of this teaching method on language teaching. Today. Since its inception in the last century, the CLT has served as a major source of influence on language teaching practices around the world. Many of the issues raised by communicative teaching methodologies remain relevant today, but newcomers to the profession may not be familiar with them. Therefore, this article serves to review what we have learned from CLT and its relevance today.